Participation of non-OECD economies in the MAD system - Leballo, Christinah (Henry Stewart Talks, 2012)
Council act of 1997, Non-OECD economy join the MAD system, MAD system for non-member economies, Evaluation of full implementation of Council Acts, Evaluation of non-member economy, Non-member participation today, Lessons learned